2022
DOI: 10.3390/nu14091732
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Golf: How Longer Courses Are Changing Athletes and Their Approach to the Game

Abstract: Nutritional guidance for competitive golfers to improve performance is limited. Recommendations and study conclusions from older research used smaller golf courses compared to today and require a reevaluation of energy expenditure. This review identifies aerobic fitness, in addition to strength, as a key determinant of success. A novel nutritional approach that incorporates carbohydrate supplementation to support aerobic fitness without sacrificing the ability to build strength is presented since longer course… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…This study of 14,108 participants showed that individuals with levels <30 ng/mL had a 58% higher chance of getting an acute respiratory infection [30]. Due to an elite golfer's schedule and travel demands, it may be a consideration to assess their baseline vitamin D level and supplement vitamin D, if required, to ensure levels are >30 ng/mL, especially during tournaments and travel where sunlight exposure may be limited [13].…”
Section: Nutrition Strategies For Travelmentioning
confidence: 99%
See 4 more Smart Citations
“…This study of 14,108 participants showed that individuals with levels <30 ng/mL had a 58% higher chance of getting an acute respiratory infection [30]. Due to an elite golfer's schedule and travel demands, it may be a consideration to assess their baseline vitamin D level and supplement vitamin D, if required, to ensure levels are >30 ng/mL, especially during tournaments and travel where sunlight exposure may be limited [13].…”
Section: Nutrition Strategies For Travelmentioning
confidence: 99%
“…Golf is viewed as a skill-based sport, in which the refinement of ball striking and putting skills has been given more emphasis than the development of physical fitness [11][12][13]. However, as mentioned previously, the course length and distances to the holes are increasing, and strength training may need to be prioritised to maximise strokes gained off the tee [13,14]. Total driving distance has been considered as either the first or second most important predictor of competitive success [13].…”
Section: Physical Attributes Of Elite Golf: Training Requirementsmentioning
confidence: 99%
See 3 more Smart Citations